Comparative study of echocardiagraphic dopppler flow velocities in left ventricular apical, mid and outflow area in patients with heart failure and normal subjects - Nordin, Mohd Hakimi (2018)
INTRODUCTION : Heart failure remained as a one of the major contributory factor for hospitalization and mortality, not only in Malaysia, but the whole world wide as well. Thus, detection at the earlier phase especially at the preclinical phase is crucial for preventive measure. Ejection fraction (EF) is one of the ECHO parameters that has been widely used, particularly to asses systolic LV function. Nevertheless, its value limited in preclinical phase and load dependence indices, thus regional wall motion abnormality assessment has been postulated as one of the modalities for LV systolic indices. This has been proven from the previous study as tissue Doppler imaging has been useful to detect regional myocardial wall strain and further studies showed myocardial wall strain rate and speckled tracking image had given an accurate measurements of regional LV wall contractility and correlate better with the global systolic function. Unfortunately, those parameters were not widely used as it required high technical skills and experience. Thus, other modalities to assess regional wall motion abnormality were studied. This study primarily design to evaluate intraventricular velocities and pressure gradient that might representing one of the modalities to asses regional LV wall contractility in a simple way yet accurate. We used earlier animal data illustrating the usefulness of those parameters in assessment of regional contractile function. METHOD AND RESULTS : This was comparative cross sectional echocardiography pilot study. Approximately 42 patients presented to HUSM with heart failure symptoms were identified and screening ECHO were done. 12 patients were excluded from this study as not fulfilled inclusion and exclusion criteria. 30 healthy volunteered from HUSM staff were recruited into normal group after screening ECHO was applied. We evaluate intraventricular velocities and pressure gradient at 3 area in LV cavity (left ventricular outflow tract (LVOT), mid and apical) which were sampled by pulse wave Doppler. Mean of intraventricular velocities and pressure gradient were recorded highest at LVOT area compare to other area among heart failure patients (1.51 and 3.01 respectively), also those values were higher if sampled towards (T) the transducer compare to away (A) the transducer in each area of LV cavity. Comparative study between heart failure patients and normal group revealed significant value (p<0.01) by using intraventricular pressure gradient that was sampled at the LVOT and mid area (away and towards the transducer). Meanwhile, no significant value in comparison between those 2 groups by using intraventricular velocities. There were no significant value in relationship between intraventricular velocities and pressure gradient with other systolic indices and ECHO parameters. CONCLUSION : Intraventricular pressure gradient remain as one of the significant modalities to asses regional wall motion abnormality if sampled at the LVOT and mid area.